Analisis Kinerja Dosen Sekolah Tinggi Agama Islam Negeri Jember: Performance Analysis of Lecturers at State Islamic College of Jember - Abdul Rahim (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2018)
Lecturer performance is a critical determinant of higher education quality, yet many institutions struggle to identify factors that significantly enhance it. This study examines the influence of compensation and motivation on lecturer performance within the context of a state Islamic college. The research aims to analyze both the partial and simultaneous effects of compensation and motivation on performance. A quantitative approach was employed, with a sample of 67 lecturers selected through random sampling from a population of 80 permanent lecturers at STAIN Jember. Data were collected using questionnaires and analyzed using path analysis with SPSS 13. The findings reveal that compensation has a significant but relatively small direct effect on performance, contributing 2.5%, while motivation demonstrates a very large direct effect, contributing 92.3%. Simultaneously, compensation and motivation together explain 98.2% of the variance in lecturer performance, with only 1.8% influenced by other unexamined factors. The study concludes that motivation is the dominant driver of lecturer performance, far outweighing the role of compensation. It is recommended that institutional leaders prioritize motivational enhancement strategies—both internal and external—over merely increasing financial compensation to optimize lecturer productivity and institutional outcomes. Kinerja dosen merupakan penentu kualitas pendidikan tinggi, namun banyak institusi masih kesulitan mengidentifikasi faktor yang secara signifikan meningkatkannya. Penelitian ini mengkaji pengaruh kompensasi dan motivasi terhadap kinerja dosen di lingkungan perguruan tinggi agama Islam negeri. Tujuannya adalah menganalisis pengaruh parsial dan simultan kompensasi serta motivasi terhadap kinerja. Pendekatan kuantitatif digunakan dengan sampel 67 dosen tetap dari populasi 80 orang di STAIN Jember yang dipilih secara acak sederhana. Data dikumpulkan melalui kuesioner dan dianalisis menggunakan analisis jalur dengan SPSS 13. Hasil penelitian menunjukkan bahwa kompensasi berpengaruh signifikan namun kecil secara langsung terhadap kinerja, yakni sebesar 2,5%, sementara motivasi memberikan pengaruh langsung sangat besar yaitu 92,3%. Secara simultan, kompensasi dan motivasi menjelaskan 98,2% variasi kinerja dosen, sisanya 1,8% dipengaruhi faktor lain yang tidak diteliti. Kesimpulannya, motivasi merupakan pendorong utama kinerja dosen, jauh melampaui peran kompensasi. Rekomendasi bagi pimpinan lembaga adalah memprioritaskan strategi peningkatan motivasi, baik internal maupun eksternal, daripada sekadar menambah kompensasi finansial untuk mengoptimalkan produktivitas dosen dan capaian institusi.